Varieties of green business : industries, nations and time - Jones, Geoffrey, 1952-; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
The concept of green business originated recently, but the phenomenon has a longer history which offers many lessons for today and the future. This book provides rich new empirical evidence on green business as it examines its variation between industries and nations, and over time. It demonstrates the deep historical origins of endeavors to create for-profit businesses that were more responsible and sustainable, but also how these strategies have faced constraints, trade-offs and challenges of legitimacy. Based on extensive interviews and archives from around the world, the book asks why green business succeeds more in some contexts than others and draws lessons from failure as well as success. This book emphasizes the importance of context for explaining the choices which explain the varieties of green business. Government policies, both local and national, cultural and religious values, and national images, are amongst the contextual factors which are identified. The book's distinctiveness lies in the use of original empirical data and the fact that it considers both successful and unsuccessful cases. An unusually wide geographical scope means that it covers not only the United States and Europe, but also less studied settings, including Chile, Costa Rica, New Zealand and Japan. Scholars and students interested in environmental management, corporate social responsibility, business ethics and trust, and business and environmental history will find this an important and fascinating read.
Contents: Preface -- 1. Varieties of business responsibility -- 2. Business and waste management in Europe before 1945 (with Andrew Spadafora) -- 3. "Power from sunshine": The business of solar energy before 1990 -- 4. Financing sustainability (with Emily Grandjean and Andrew Spadafora) -- 5. Organic food and national image: the paradox of New Zealand (with Simon Mowatt) -- 6. Creating the market for organic wine: sulfites, certification, and green values (with Emily Grandjean) -- 7. Creating ecotourism in Costa Rica (with Andrew Spadafora) -- 8. Alternative paths of green entrepreneurship: Yvon Chouinard, Doug Tompkins and Kristine McDivitt Tompkins (with Ben Gettinger) -- Postscript -- Index.
Includes index.
Description based on print record.
Keywords: Business -- Environmental aspects; Electronic books